Longitudinal sawing of the round lumbers orientated to generatrix - Somar, Andriy; Somar, Galyna (Forestry, Forest, Paper and Woodworking Industry, 2007)
The longitudinal sawing of logs considered for the variant of basing to generatrix was considered. Fields of dispersion and ranges of lumber recovery changes under round lumber sawing were determined. The squaring scheme was used for determination of indicated factors.